Therapeutic Drug Monitoring by Pharmacists: Does It Reduce Costs? - Pedro Cardoso; C. Santos; Francisco Rocha-Gonçalves (Global Journal on Quality and Safety in Healthcare, 2020)
Therapeutic drug monitoring (TDM) has as its main objective to ensure that the plasma drug concentration remains within the appropriate range. Regarding the economic dimension of TDM, it is known that there are gains in health outcomes; however, there is still little evidence for the benefit of this procedure performed by pharmacists within the hospital context. With this project, we aimed to create a matrix of cost avoidance associated with TDM performed by pharmacists and to quantify the total avoided costs in 1 year, by implementing a TDM process in a tertiary hospital. For the studied period, we collected 362 pharmaceutical interventions related to TDM of antibiotics performed in adults. As a result, considering these data, the total cost avoidance in 1 year was 371,018€ ($416,584.58) at one medical center. We conclude that TDM is highly cost-avoidant and that the implementation costs by pharmaceutical services is clearly lower than the benefit achieved.